Cryptophlebia Walsingham, 1900, Thaumatotibia Zacher, 1915, and Archiphlebia Komai & Horak, 2006, in Australia (Lepidoptera: Tortricidae: Olethreutinae: Grapholitini) - Horak, Marianne; Komai, Furumi (Zootaxa, 2016)
The Australian species of the grapholitine genera Cryptophlebia Walsingham, 1900, Thaumatotibia Zacher, 1915 and Archiphlebia Komai & Horak, 2006, are revised, described and illustrated. A key to species is provided. Five named species of Cryptophlebia, C. ombrodelta (Lower), C. iridosoma (Meyrick), C. rhynchias (Meyrick) and C. pallifimbriana Bradley, are redescribed and three new species, C. wraggae, sp. nov., C. stigmata, sp. nov., and C. caulicola, sp. nov., are described. Cryptophlebia amblyopa Clarke, described from Micronesia, is synonymised with C. iridosoma. Cryptophlebia caulicola, sp. nov., is a borer in twigs of Acacia mangium Willd. in northern Queensland. Thaumatotibia aclyta (Turner) and T. zophophanes (Turner) are redescribed and the new species T. maculata, sp. nov., is described. Fruit of Acronychia spp. (Rutaceae) have been identified as native hosts of T. zophophanes, a pest species which damages macadamia (Proteaceae) and avocado (Lauraceae) on the Atherton Tableland. Archiphlebia endophaga (Meyrick) and A. rutilescens (Turner) are redescribed, and the new species A. gilva, sp. nov., is described.